DEVELOPING OF PERSONAL LEADERSHIP LEARNING MODEL FOR VOCATIONAL SCHOOL STUDENTS - Dana Rizki Nur Adnan (Universitas Negeri Yogyakarta, 2019)
This study was aimed at developing and investigating the feasibility of the personal leadership learning model for vocational students in the Mechanical Engineering Expertise Program. The personal leadership learning model used in this study is a learning model adapted from Scouller's personal leadership model. The subjects in this study were students of class X of the Mechanical Engineering Department of 2017/2018 and the teachers, while the object of research was the personal leadership model. Research and development approach was used in this study with the development procedure including data collection and analysis, initial product development, validation, product testing, revision, and final product. The data were gathered by interviews, observations, and survey. The data then were analyzed using qualitative descriptive method. The results of the study produce a personal leadership learning model which is declared by material experts and expert learning models, as a feasible and applicable model. Personal leadership learning model is effective in improving students' activity, especially in asking or giving opinion.PENGEMBANGAN MODEL PEMBELAJARAN PERSONAL LEADERSHIP PADA SISWA SEKOLAH MENENGAH KEJURUANPenelitian ini bertujuan mengembangkan dan menguji kelayakan model pembelajaran personal leadership untuk siswa SMK Program Keahlian Teknik Pemesinan. Model pembelajaran personal leadership yang digunakan dalam peneltian ini merupakan model pembelajaran yang diadaptasi dari model personal leadership menurut Scouller. Subjek dalam penelitian ini adalah siswa kelas X Jurusan Teknik Pemesinan 2017/2018 dan Guru SMK, sedangkan objek penelitian adalah model personal leadership. Pendekatan penelitian dan pengembangan (Research Development) digunakan dalam penelitian ini dengan prosedur pengembangan mencakup analisis dan pengumpulan data, pengembangan produk awal, validasi, uji coba produk, revisi, dan produk akhir. Pengumpulan data dilakukan dengan wawancara, observasi, dan survei. Data dianalisa dengan menggunakan metode deskriptif kualitatif. Hasil penelitian menyatakan bahwa model pembelajaran personal leadership yang dikembangkan dinyatakan sangat layak oleh ahli materi dan ahli model pembelajaran, serta dinyatakan dapat diterapkan dalam proses pembelajaran oleh siswa dan guru. Model pembelajaran personal leadership efektif dalam meningkatkan aktivitas siswa, terutama dalam aktivitas bertanya atau berpendapat.